1994
DOI: 10.1111/j.1540-8191.1994.tb00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Continuous Retrograde Cerebral Perfusion on the Brain During Deep Hypothermic Systemic Circulatory Arrest

Abstract: Deep hypothermic circulatory arrest has been widely used as an adjunct for surgery of the aortic arch to protect the brain and other vital organs. We introduced the use of continuous retrograde cerebral perfusion via the superior vena cava during deep hypothermic circulatory arrest in 1987 and have used it in 33 patients. Continuous retrograde cerebral perfusion times ranged from 10 to 89 minutes (mean 40.2 +/- 22.5), and minimal nasopharyngeal temperatures ranged from 14 to 25 degrees C (mean 17.4 +/- 2.0). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Although dogs are not precisely suitable as the experimental model :for RCP because of the small internal jugular vein with many venous valves [7], in this experimental study, blood infusion for RCP was performed directly into the temporal sinus bilaterally via the internal maxillary veins with no venous valves. It is unclear whether aerobic metabolism proceeds as a result of the oxygen provided to the brain during RCP, however, RCP may wash out the accumulated metabolite and can maintain brain temperature at an optimal level during RCP as a result of the cold blood perfusate being infused [8].…”
Section: Discussionmentioning
confidence: 99%
“…Although dogs are not precisely suitable as the experimental model :for RCP because of the small internal jugular vein with many venous valves [7], in this experimental study, blood infusion for RCP was performed directly into the temporal sinus bilaterally via the internal maxillary veins with no venous valves. It is unclear whether aerobic metabolism proceeds as a result of the oxygen provided to the brain during RCP, however, RCP may wash out the accumulated metabolite and can maintain brain temperature at an optimal level during RCP as a result of the cold blood perfusate being infused [8].…”
Section: Discussionmentioning
confidence: 99%
“…The effluent blood is desaturated, suggesting cerebral oxygen extraction. 44,57 In our own studies of carotid artery effluent during RCP, we have found significant transcranial glucose and oxygen extraction (mean 1 µmol/l and 22 ml/ml, respectively). However, the low effluent pO 2 (mean 14 mmHg), and high glucose extraction suggest ongoing cerebral ischaemia (unpublished observations).…”
Section: Is There Evidence That Rcp Perfuses the Brain In Humans?mentioning
confidence: 94%
“…Other developments such as the use of deep hypothermia, the utilization of total circulatory arrest and more efficient methods for myocardial and cerebral protection, improved the immediate and long-term results of the surgical procedure of these frequently challenging afflictions [8,9]. Among these developments is the use of man-made materials of synthetic fibers, which are making the aortic aneurysmal segment replacement the procedure of choice for this disease [10,11].…”
Section: Commentsmentioning
confidence: 99%